Temptations toward behaviors minimizing energetic costs (BMEC) automatically activate physical activity goals in successful exercisers. (May 2017) - Cheval, Boris; Sarrazin, Philippe; Boisgontier, Matthieu P.; Radel, Remi
Abstract: Objectives: With regard to the pivotal role of physical activity (PA) in health protection, understanding how individuals maintain regular PA despite ubiquitous opportunities to adopt behaviors minimizing energetic costs (BMEC) appears crucial. The purpose of the present research was to test whether BMEC primes act as temptations and activate PA goals in successful exercisers. Design: Within and between-subjects experiments. Methods: Students in sports science (Experiment 1; N = 46) and individuals with high value of PA goals and low versus high PA levels (Experiment 2; N = 28) performed a primed-lexical decision task. Results: Experiment 1 revealed that BMEC primes facilitated the recognition of PA-related words, whereas PA primes did not facilitate the recognition of words related to BMEC. Experiment 2 showed that this facilitative effect was specific to individuals who were successful in reaching their PA goals. Conclusions: BMEC act as temptations that automatically activate the representation of PA goals in individual who manage to maintain regular PA. Highlights: BMEC act as temptations threatening physical activity goals. BMEC primes activated physical activity goals in successful exercisers. BMEC-triggered physical activity activation explains self-regulation success.